Human development in South Asia - Haq, Mahbub ul; South Asia Conference on the Legacy of Mahbub ul Haq-Human Development (2000 : New Delhi, India); Institute of Social Sciences (New Delhi, India) (Oxford : University press, 1997)
Contributed articles presented at a seminar organized by Institute of Social Sciences, New Delhi, India.
Includes bibliographical references.
Keywords: Human capital -- South Asia -- Congresses; South Asia -- Economic policy -- Congresses; South Asia -- Social policy -- Congresses